(untitled) (Contemporary Journal of Social Science Review, 2025)
India apparently used hybrid warfare methods in Baluchistan, which might be a big source of worry for South Asian security and, as a result, a factor undermining CPEC. The purpose of this study is to demonstrate how India seems to have gained influence in the Baluchistan region, as well as the methods and repercussions on the CPEC. This study presents an argument for the idea that there is concrete proof of India’s use of covert techniques as part of its hybrid warfare strategy, based on a detailed examination of current events and specific academic works on the subject. As a result of the project’s viability and security concerns, Pakistan constructed additional security measures along the CPEC route to effectively manage the situation. The conclusion of the study paper emphasises the importance of cross-regional and international partnerships, assistance investment in Baluchistan’s development, the implementation of hybrid warfare counter-measures, increased security measures, and effective diplomatic communication. This article is produced in a strategic manner to address the complicated concerns regarding India’s involvement in Baluchistan and their impact on the CPEC, ultimately demonstrating the benefit of the South Asian area via the development and spread of information and, finally, the realisation of peace.